2011
DOI: 10.1007/s10495-011-0663-4
|View full text |Cite
|
Sign up to set email alerts
|

p66Shc-dependent apoptosis requires Lck and CamKII activity

Abstract: p66Shc, an adaptor molecule which enhances reactive oxygen species (ROS) production by mitochondria, promotes T-cell apoptosis by inducing mitochondrial dysfunction and impairing Ca(2+) homeostasis. We have addressed the potential role of Lck, a kinase which has been implicated in T-cell apoptosis induced by a number of stimuli, in the proapoptotic activity of p66Shc. Lck deficiency in Jurkat T cells overexpressing p66Shc leads to impaired apoptotic responses to supraphysiological increases in [Ca(2+)](c). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Given the central role of Lck as the initiator kinase in TCR signaling (37), it can be hypothesized that GroPIns4 P has the ability to modulate T-cell activation. Lck has also been implicated in the regulation of T-cell apoptosis induced by a wide range of stimuli, including prolonged TCR stimulation (45) and treatment with sphingosine (46), and it is also an essential component of the signaling pathways that control Ca 2+ -mediated T-cell apoptosis, which involve both the conformational activation of Bax and the expression of proapoptotic Bcl-2 family members (47). How TCR engagement can lead to cell fates as diverse as activation, anergy, and apoptosis is one of the fundamental and as yet open questions in immunology.…”
Section: The Gpis As Modulators Of T-cell Functions: Facts and Hypothmentioning
confidence: 99%
“…Given the central role of Lck as the initiator kinase in TCR signaling (37), it can be hypothesized that GroPIns4 P has the ability to modulate T-cell activation. Lck has also been implicated in the regulation of T-cell apoptosis induced by a wide range of stimuli, including prolonged TCR stimulation (45) and treatment with sphingosine (46), and it is also an essential component of the signaling pathways that control Ca 2+ -mediated T-cell apoptosis, which involve both the conformational activation of Bax and the expression of proapoptotic Bcl-2 family members (47). How TCR engagement can lead to cell fates as diverse as activation, anergy, and apoptosis is one of the fundamental and as yet open questions in immunology.…”
Section: The Gpis As Modulators Of T-cell Functions: Facts and Hypothmentioning
confidence: 99%
“…CaMKII, a multifunctional heteromeric serine/threonine protein kinase, is activated by both Ca 2+ and oxidative stress (Erickson et al, 2008). Increases in CaMKII activity have been reported to correlate with cell apoptosis, myocardial ischemia/reperfusion injury and cell excitotoxic insult (Ling et al, 2013;Patrussi et al, 2012) . Our results suggested that baicalin mediated a protective effect by preventing inhibition of neuronal death from apoptosis through regulation of [Ca 2+ ] i and further attenuating the phosphorylation level of CaMKII in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its ability to inhibit survival signaling at multiple levels, p66SHC increases the susceptibility of lymphocytes to cellular stress, promoting apoptosis (Pellegrini et al, 2007;Capitani et al, 2010). Pharmacological or physiological apoptotic stimuli induce p66SHC phosphorylation on S36 through a mechanism requiring Ca 2+ calmodulin-dependent kinase and the tyrosine kinase LCK (Pacini et al, 2004;Patrussi et al, 2012). S36-phosphorylated p66SHC promotes apoptosis by impairing both mitochondrial function and Ca 2+ homeostasis (Pellegrini et al, 2007).…”
Section: P66shc Regulates Survival Signaling and Apoptosis In Lymphocmentioning
confidence: 99%